Exploring the potential of spray-dried blackberry powder enriched with zinc and folic acid as a nutritional alternative for children and pregnant women (2024)
ABSTRACT: Currently, strategies to achieve the Sustainable Development Goals (SDGs) are being sought worldwide. Accordingly, this study seeks to contribute to achieving SDGs 2 (Zero Hunger) and 3 (Good Health and Well-being) by addressing nutritional deficiencies in pregnant women and children. These vulnerable populations worldwide have malnutrition problems associated with a lack of zinc and folic acid, causing them health problems. This research aimed to develop a blackberry powder fortified with zinc and folic acid obtained by spray drying as a nutritional alternative for children and pregnant women. The blackberry was characterized according to the AOAC, an optimization of the spray drying process with a central composite experimental design. The powder’s bulk and tapped density, solubility, and anthocyanin content were determined. The variation in zinc and folic acid content over a storage period was measured. The moisture content of the fresh blackberries was 89%. The solubility and anthocyanin content of blackberry powder were 86% and 0.263 mg cyanidin-3-glucose/g, respectively. The optimal spray drying conditions were: 23.6% solid content and an air inlet temperature of 167.92 °C. The bulk density of the powder did not change with storage time (p>0.05); the zinc and folic acid content in blackberry powder was 144 and 90 (μg/100 g), respectively. A blackberry powder fortified with zinc and folic acid was obtained by spray drying, guaranteeing 30% of the daily nutritional requirement for pregnant women and children, in a 50-gram portion of powder.